The phenomenon of incest obscenity: Social network and sentiment analysis on YouTube - Iwan, Iwan; Firando, Elvina Ekga; Paramitha, Aulia; Bakry, Gema Nusantara (Universitas Padjadjaran, 2025)
Background: Freedom in digital transformation development has led to abuse, resulting in sexual harassment, such as the “incest fantasy” community. This community sparked public controversy because it deviated from the norm. Despite the bans and arrests, people are still talking about this issue. Comments on YouTube videos are one example. Purpose: Observing sentiment polarization on comments and mapping dominating actors are the goals of this research. Method: This research maps and analyzes the network established by YouTube video and comments linked to the “incest fantasy” group using a Social Network Analysis (SNA) technique, which uses quantitative approaches. Results: The tvOneNews channel has the greatest centrality degree (CD = 27; CC = 0.88; CB = 0.022) according to the findings. A central community is shown via an analysis of comments on TVOneNews programming, encircled by several smaller groups or individuals. This indicates that YouTube comments are not a space for social discourse. The average sentiment level is moderate, indicating that the public is neither overly biased nor neutral, but rather tends toward criticism. Conclusion: There is a dominant actor in the network, but their role is merely a trigger and does not significantly influence the discourse. Analysis of the comments also indicates polarization, with neutral sentiment predominating. Implications: This research enriches communication studies by applying graph theory to enable network mapping and monitoring of discourse development in comments.